2014
DOI: 10.1177/00333549141291s114
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of the Viral Hepatitis-HIV Syndemic in San Francisco: A Collaborative Surveillance Approach

Abstract: Objectives. To describe the epidemiology of people coinfected with hepatitis B virus (HBV) or hepatitis C virus (HCV) and HIV in San Francisco, the San Francisco Department of Public Health's Communicable Disease Control and Prevention Section and the HIV Epidemiology Section collaborated to link their registries .Methods. In San Francisco, hepatitis reporting is primarily through passive laboratory-based surveillance, and HIV/AIDS reporting is primarily through laboratory-initiated active surveillance . We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
5
12
1
Order By: Relevance
“…This is consistent with other studies that have found that male sex, black race, and Hispanic ethnicity are associated with higher risk of HIV co-infection with HBV and HCV [10, 12, 17]. The HIV transmission risk categories of individuals at highest risk for HIV co-infection with HBV or HCV in NYC were also consistent with the transmission routes of and reported risk factors for HBV and HCV [10, 11, 1316, 18]. The largest proportion of HIV/HBV-infected individuals were MSM, while the largest proportion of HIV/HCV-infected and HIV/HBV/HCV-infected individuals had a history of IDU.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with other studies that have found that male sex, black race, and Hispanic ethnicity are associated with higher risk of HIV co-infection with HBV and HCV [10, 12, 17]. The HIV transmission risk categories of individuals at highest risk for HIV co-infection with HBV or HCV in NYC were also consistent with the transmission routes of and reported risk factors for HBV and HCV [10, 11, 1316, 18]. The largest proportion of HIV/HBV-infected individuals were MSM, while the largest proportion of HIV/HCV-infected and HIV/HBV/HCV-infected individuals had a history of IDU.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple clinical cohort and cross-sectional studies have studied the prevalence of and risk factors for HBV and HCV co-infection in groups of people living with HIV/AIDS (PLWHA) throughout the world [7,[10][11][12][13][14]. Another important method for assessing the prevalence of HIV co-infection with HBV and/or HCV and the characteristics of co-infected patients is to match surveillance data for each infection collected by state or local health departments [15][16][17][18]. Surveillance data are derived from large, geographically well-defined populations and include all positive tests reported to health departments; therefore, such data are more representative than data from highly specialized clinical studies, which are limited to patients selected for enrolment.…”
Section: Introductionmentioning
confidence: 99%
“…The demography of the cohort of coinfected persons in our study matched that of other US studies regarding race and sex [2327]. HIV transmission categories were correlated with the most common viral hepatitis transmission risks in the USA (sexual transmission for HBV and IDU for HCV) [3, 31, 32].…”
Section: Discussionsupporting
confidence: 61%
“…The prevalence of HIV coinfection among CHB patients found in our study is slightly lower than the estimates published from other low HIV-prevalence settings (United States) of 5.2%–6.3% among CHB patients [26, 27], whereas the overall HIV coinfection prevalence of 5.3% among CHC patients found in our study was similar to estimates found in larger CHC patient cohorts from the United Kingdom (UK) and the United States at 5.0% and 4.3%, respectively [27, 28].…”
Section: Discussioncontrasting
confidence: 82%